DiABlu: Digital Arts' Bluetooth - Cardoso, Jorge C. S. (2011)
Abstract: Digital art installations can often gain from the capability of detecting the presence of people observing them. With this information, the artists can enhance the experience of who interacts with their work. While this detection can be made by means of web cameras or sensors, these systems are generally difficult to implement for people with a low knowledge of programming. We propose a system that uses bluetooth to do this detection and allows easy integration with applications often used by digital artists. The system also allows users to interact with the installation using their mobile devices. It's intended to be used in art installations by digital artists who wish to give their audience a new way to interact with their pieces.